Pathological Study of a FMR1 Premutation Carrier With Progressive Supranuclear Palsy - Paucar, Martin; Nennesmo, Inger; Svenningsson, Per (Frontiers in Genetics, 2018)
Dual pathology in fragile X mental retardation 1 (FMR1) premutation carriers and fragile X–associated tremor/ataxia syndrome (FXTAS) patients is an emerging phenomenon. Although it includes atypical parkinsonism, neuropathological confirmation is very scarce. Here, we describe neuropathological findings for a female who suffered a severe parkinsonian syndrome with apraxia and supranuclear palsy. She died at the age of fifty, six years after the initial diagnosis. Prominent neuronal loss was found in the pallidum, subthalamic nucleus, and tectum, but the loss of Purkinje cells was rather mild. Intranuclear inclusions containing ubiquitin and FMRpolyglycine, a pathological hallmark of FXTAS, were detected in neurons and astrocytes. However, this inclusion pathology was overshadowed by a very prominent four repeat tau accumulation in tufted astrocytes, oligodendroglial coiled bodies, thread structures, and neurons. This is, to best of our knowledge, the first report describing a pathologically confirmed progressive supranuclear palsy - corticobasal syndrome (PSP-CBS) variant case in a FMR1 premutation carrier.